Redox metabolism in Trypanosoma cruzi: functional characterization of tryparedoxins revisited - Arias, Diego Gustavo (2013)
Tryparedoxins (TXNs) are multipurpose oxidoreductases from trypanosomatids that transfer reducing equivalents from trypanothione to different thiol proteins. In Trypanosoma cruzi, two genes coding for TXN like proteins have been identified: TXNI, previously characterized as a cytoplasmic protein, and TXNII, a putative tail-anchored membrane protein. In this work, we performed a comparative functional characterization of T. cruzi TXNs. Particularly, we cloned the gene region coding for the soluble version of TXNII for its heterologous expression. The truncated recombinant protein (without its 22 C-terminal transmenbrane amino acids) showed TXN activity. It was also able to transfer reducing equivalents from trypanothione, glutathione or dihydrolipoamide to different acceptors, including methionine sulfoxide reductases and peroxiredoxins. Results support the occurrence and functionality of a second tryparedoxin, which appears as a new component in redox scenario in T. cruzi.